Entrepreneurship in University Islamic Education Constructivism Perspective - Bachtiar Hariyadi (EDUCATIO : Journal of Education, 2019)
Constructivism, as a philosophical paradigm, seems to be a good explanation in understanding the entrepreneurial learning process that builds meaning through experience with the business world. This study aims to explore the learning process of student entrepreneurship from a constructivist perspective and try to understand how students learn to become entrepreneurs in the context of higher education. This research is based on the learning of a small group of Sharia Economics study program students who take entrepreneurship modules at Sunan Giri University Surabaya Indonesia. The results of the study indicate that the student learning process is seen as a very valuable experience and is based on all types of interactions in the classroom according to the situation outside their class. Entrepreneurship development is supported by an experience approach to learning, action-based and student-centered, focusing on developing skills and competencies related to entrepreneurship.